Size Matters: The Role of Nodule Size in Assessing Lithic Transportation—The Case of the Mount Reihan Flint Extraction and Axe/Adze Workshop, Dishon Basin, Eastern Galilee, Israel. (3rd July 2018) - Finkel, Meir; Gopher, Avi
ABSTRACT: There has been much progress recently in reconstructing the transportation of lithic materials from quarry/extraction sites and workshops to occupation sites. The suggested "theoretical nodule, " "cortex ratio, " and "volume ratio" measures have proven useful, mainly when applied to cases in which relatively small initial nodules/cobbles were selected for knapping. However, these methods lose much of their relevance when dealing with the production of bifacials from large nodules. In this article, we present evidence from a newly discovered axe/adze workshop at Mount Reihan in the eastern Galilee, Israel, which boasts an almost complete chaîne opératoire of the production of Neolithic/Chalcolithic axes and adzes from large (mean weight 17.7 kg) flint nodules as a starting point. Measuring nodules, bifacial roughouts, and debitage enables us to propose a two-step method that is valid for the production of bifacials from large nodules: (1) weight of knapped waste is calculated as 80 per cent of the initial flint weight; (2) the 20 per cent weight that remains is divided between the rejected roughouts and the exported/transported items, following a ratio of 1 roughout: 2–3 exported tools.